Pixel level decorrelation in service of the Spitzer microlens parallax survey. Issue 4 (6th August 2020) - Dang, Lisa; Calchi Novati, S; Carey, S; Cowan, N B
ABSTRACT: Microlens parallax measurements combining space-based and ground-based observatories can be used to study planetary demographics. In recent years, the Spitzer Space Telescope was used as a microlens parallax satellite. Meanwhile, Spitzer IRAC has been employed to study short-period exoplanets and their atmospheres. As these investigations require exquisite photometry, they motivated the development of numerous self-calibration techniques now widely used in the exoplanet atmosphere community. Specifically, pixel level decorrelation (PLD) was developed for starring-mode observations in uncrowded fields. We adapt and extend PLD to make it suitable for observations obtained as part of the Spitzer Microlens Parallax Campaign. We apply our method to two previously published microlensing events, OGLE-2017-BLG-1140 and OGLE-2015-BLG-0448, and compare its performance to the state-of-the-art pipeline used to analyses Spitzer microlensing observation. We find that our method yields photometry 1.5–6 times as precise as previously published. In addition to being useful for Spitzer, a similar approach could improve microlensing photometry with the forthcoming Nancy Grace Roman Space Telescope .